Neoadjuvant and Adjuvant Chemotherapy for Variant Histology Bladder Cancers: A Systematic Review and Meta-Analysis - Zhu, Ziwei; Xiao, Yunyuan; Hu, Shengye; Wang, Ziyuan; Zhu, Zaisheng (Frontiers in Oncology, 2022)
Context: To improve the prognosis of variant histology (VH) bladder cancers, clinicians have used neoadjuvant chemotherapy (NAC) or adjuvant chemotherapy (AC) on the basis of radical cystectomy (RC). Despite some new data, the evidence remains mixed on their efficacy. Objective: To update the current evidence on the role of NAC and AC for VH bladder cancers. Evidence acquisition: We searched for all studies investigating NAC or AC for bladder cancer patients with variant histology in PubMed, Embase, and the Cochrane Central Register of Controlled Trials up to December 2021. The primary end points were recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS). Evidence synthesis: We identified 18 reports comprising a total of 10192 patients in the NAC studies. In patients with VH, the use of NAC did improve CSS (hazard ratio [HR] 0.74, 95% confidence interval [CI] 0.55–0.99, p = 0.044), and OS (HR 0.74, 95% CI 0.66–0.84, p = 0.000), but not RFS (HR 1.15, 95% CI 0.56–2.33, p = 0.706). Subgroup analyses demonstrated that receiving NAC was associated with better OS in sarcomatoid VH (HR 0.67, 95% CI 0.54–0.83, p = 0.000) and neuroendocrine VH (HR 0.54, 95% CI 0.43–0.68, p = 0.000). For AC, We identified 8 reports comprising a total of 3254 patients. There was a benefit in CSS (HR 0.61, 95% CI 0.43–0.87, p = 0.006), and OS (HR 0.76, 95% CI 0.60–0.98, p = 0.032). Subgroup analyses demonstrated that only neuroendocrine VH had better CSS (HR 0.29, 95% CI 0.13–0.67, p = 0.174) when received AC. Conclusions: NAC or AC for VH bladder cancers confers an OS and CSS benefit compared with RC alone. For NAC, the benefit was independently observed in the sarcomatoid and neuroendocrine subgroups. As for AC, only neuroendocrine subgroups improved CSS.